A Comparison of LC-MS/MS and a Fully Integrated Autosampler/Solid-Phase Extraction System for the Analysis of Protein Binding Samples. (July 2016) - Amaral, Adam; Saran, Chitra; Amin, Jakal; Hatsis, Panos
A new analysis approach was evaluated for measuring plasma protein binding (PPB) of small molecules using the Agilent RapidFire high-throughput system coupled with a Sciex API 4000 mass spectrometer (RF-MS/MS). Thirty-three proprietary and 12 literature compounds were subjected to rapid equilibrium dialysis (RED) and evaluated in parallel using RF-MS/MS at 16.4 s/sample and traditional liquid chromatography–tandem mass spectrometry (LC-MS/MS) at 3.5 min/sample, thus making the RF-MS/MS analysis over 12 times faster than LC-MS/MS. The high-throughput analysis method that was developed demonstrated excellent correlation with the traditional LC-MS/MS analysis method with an r 2 value of 0.96. The RF-MS/MS analysis method was implemented to increase sample throughput, decrease turnaround time for PPB data, and decrease time burden on existing LC-MS/MS instruments.